2021
DOI: 10.1371/journal.pone.0247246
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, not regulation tendency, predicts how individuals regulate in the laboratory: An exploratory comparison of self-report and psychophysiology

Abstract: Anxiety influences how individuals experience and regulate emotions in a variety of ways. For example, individuals with lower anxiety tend to cognitively reframe (reappraise) negative emotion and those with higher anxiety tend to suppress negative emotion. Research has also investigated these individual differences with psychophysiology. These lines of research assume coherence between how individuals regulate outside the laboratory, typically measured with self-report, and how they regulate during an experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
(157 reference statements)
0
7
0
Order By: Relevance
“…These were categories of stimuli that were chosen to be similar to previous investigations of emotion regulation ( McRae et al, 2010 ), and these stimuli are discussed in the Supplementary Material . These picture stimuli are further analyzed and discussed in Burr et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…These were categories of stimuli that were chosen to be similar to previous investigations of emotion regulation ( McRae et al, 2010 ), and these stimuli are discussed in the Supplementary Material . These picture stimuli are further analyzed and discussed in Burr et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…For example, studies have shown that reappraisal of negative emotion is associated with reduced activity of the corrugator supercilii (associated with anger, sadness, and fear) with d = − 0.32 5 . In addition, the levator labii superioris (associated with disgust) has also been associated with reduced activity during reappraisal 6 . Similar effects have been reported for suppression 6 , distancing 7 , and distraction 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the levator labii superioris (associated with disgust) has also been associated with reduced activity during reappraisal 6 . Similar effects have been reported for suppression 6 , distancing 7 , and distraction 8 . Importantly, results on electromyographic measures seem to be more consistent compared to other autonomic measures, likely because they are specific to emotional valence and its changes.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the large majority of studies have relied on single retrospective assessments of the habitual use of emotion regulation (i.e., global, trait-like assessments of the strategies that are typically used), which, on the one hand, are susceptible to recall limitations and generalization biases, and, on the other, fail to account for within-individual variability. People draw on different knowledge when reporting global (e.g., how you think you are in general) versus momentary (e.g., how you think you are at present) characteristics of emotion 14 , and there is evidence that reports of the habitual use of emotion regulation strategies have low ecological and discriminant validity in relation to the spontaneous use of those strategies in daily life 15 17 . For example, self-reported habitual reappraisal predicts not only reappraisal use in daily life, but also rumination and suppression use 16 .…”
Section: Introductionmentioning
confidence: 99%